ETIOLOGICS AND AGGRAVATION FACTORS OF CHRONIC HEART FAILLURE IN A SUB SAHARAN INTRA-HOSPITAL MILIEU. (June 2018) - Ouankou, C. Ngongang; Kapi, L.O. Chendjou; Tachim, K.; Tsambang, L.; Ngamga, J. Wandji; Etoundi, A.; Essono, A.; Tsamo, C.; Soule, I.L. Nchoua; Ouankou, M.D.; Kowo, M.; Mfeukeu, L. Kuate; et al.
Abstract : Objective: The objective of this study was to determine the main etiologic and aggravation factors of chronic heart failure and to evaluate their impact on the life quality of patients from a referral hospital of Cameroon. Design and method: It consisted in a prospective study, including all newly diagnosed patients with chronic heart failure (less than one year ago), as well as patients with acute decompensation on a chronic background (included after being stabilised for at least 2 months). Were included patients with clinical and echocardiographic signs of heart failure. Results: In all, we enrolled 40 patients. The mean age was of 64 years. The sex ratio was of 0.48. Hypertension (55%) was the most encountered etiologic factor. The main cardiovascular risk factors were: physical inactivity (72.5 %), dyslipidemia (50%), and alcohol consumption (37.5%). Dyspnoea was always present. The other biological perturbations were: an elevation of gamma GT (77.5%), hyperuricemia (75%), an elevation of free bilirubin (65%). The atrial fibrillation was 20% and Natriuretic peptide abnormal. The echocardiography shown 40% of the patients with a preserved left ventricular function, 37% with a severe systolic dysfunction of the left ventricle, and 23% had an intermediary ejection fraction. More than half the number enrolled (63.2%) had a low resistance to effort with a walk perimeter below 300 meters in 6 minutes. Hypertensive cardiomyopathy (45%) represented the main cause, closely followed by dilated cardiomyopathy (17.5%). About the life quality test, next to one-quarter (73%) of the study population lived very poorly their heart failure, mostly when many etiologic and aggravation factors were found in the same individual. Beta-blockers (90%) represented the most used pharmacological class, followed by Loop Diuretics (72.5%) and Angiotensin converting enzyme inhibitors (62.5%). Two (2) patients were placed on dobutamine following a cardiogenic choc (with hypotension). The mortality rates at D30 Conclusions: In Cameroon chronic heart failure arise towards sixty years, with hypertension as principal etiologic factor. The research, prevention and correction of these factors constitute important steps to its management, since it greatly improves the follow-up of patients and in such doing improves their prognosis.